In vitro synergy of antibiotic combinations against planktonic and biofilm Pseudomonas aeruginosa - Ghorbani, Hossein; Memar, Mohammad Yousef; Sefidan, Fatemeh Yeganeh; Yekani, Mina; Ghotaslou, Reza (German Medical Science GMS Publishing House, 2017)
Aim: The combination of different antimicrobial agents and subsequent synergetic effects may be beneficial in treatment of infections. The aim of the present study was to determine antibiotic susceptibility patterns of clinical isolates of and the effect of different antibiotic combinations against the multidrug-resistant (MDR), biofilm-producing bacterium . Methods: Thirty-six clinical isolates were evaluated. The disk diffusion method was performed to determine antibiotic susceptibility patterns according to the Clinical and Laboratory Standards Institute (CLSI) guidelines. The minimum inhibitory concentration of antimicrobial agents for the test organisms was determined by the broth microdilution method. To determine synergetic effects of the combinations of agents, the checkerboard assay and the fractional inhibitory concentration were used. The biofilm inhibitory concentration was determined to detect any inhibitory effect of antibiotics against the biofilm. Results: High levels of resistance were detected against most antibiotics, except colistin and polymyxin. According to the disk diffusion method, 58.3% of isolates were MDR. A synergetic effect between amikacin/ceftazidime, tobramycin/colistin and ceftazidime/colistin was found in 55.6%, 58.3% and 52.8% of isolates, respectively. A significant synergetic effect against biofilm-producing isolates was observed for the combination of tobramycin (0.5-1 µg/ml) and clarithromycin (256-512 µg/ml).Conclusion: Combinations of antibiotics have a different activity on the biofilm and planktonic forms of . Consequently, separate detection of antibacterial and antibiofilm effects of the antibiotic combinations may be useful in guiding the antibiotic therapy.